2017
DOI: 10.4172/2376-127x.1000336
|View full text |Cite
|
Sign up to set email alerts
|

Study of Urinary Uric Acid and Creatinine Ratio as a Marker of Perinatal Asphyxia and Its Correlation with Different Stages of Hypoxic Ischemic Encephalopathy

Abstract: Background: Birth asphyxia is one of the leading causes of neonatal mortality in India. Hypoxic-ischemic encephalopathy (HIE) is the neurological manifestation of systemic hypoxia in new-born. 20-25% of asphyxiated babies who exhibit severe HIE, die during the new-born period. The most commonly used diagnostic and prognostic index to evaluate asphyxia in neonates is APGAR score but alone it is not useful to ferret out neurological outcome. Now-a-days uses of biomarkers enable the clinicians to screen infants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Our study showed a significant higher ratio of UUA/ Cr in premature neonates admitted in NICU suffering hypoxia. Several other studies have reached similar results [2,3,6,8,9,[13][14][15][16][17][18][19][20][21]. In the case -control study of Sreekrishna et al on 50 normal neonates and 50 newborn infant with asphyxia, the mean Urinary Uric Acid / Cr ratio in case and control group was 2.8 ± 0.9 and 0.8 ± 0.2 respectively which shows a significant higher ratio in case group (P < 0.001) [2].…”
Section: Discussionsupporting
confidence: 59%
“…Our study showed a significant higher ratio of UUA/ Cr in premature neonates admitted in NICU suffering hypoxia. Several other studies have reached similar results [2,3,6,8,9,[13][14][15][16][17][18][19][20][21]. In the case -control study of Sreekrishna et al on 50 normal neonates and 50 newborn infant with asphyxia, the mean Urinary Uric Acid / Cr ratio in case and control group was 2.8 ± 0.9 and 0.8 ± 0.2 respectively which shows a significant higher ratio in case group (P < 0.001) [2].…”
Section: Discussionsupporting
confidence: 59%
“…There are not many studies that determine the utility of UA/Cr as a marker for the outcome. Choudhary et al [13] proved a significant positive correlation between the urine UA/Cr and different stages of HIE classified according to Sarnat and Sarnat staging. Urine UA/Cr was significantly higher in severe HIE (3.61±0.61) when compared to neonates with moderate HIE (2.95±0.98) and mild HIE (2.64±0.25) with a p<0.001.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio was significantly higher in severe HIE (3.61±0.61) when compared with moderate HIE (2.95±0.98) and with mild HIE (2.64±0.25, p<0.01). [19] As the number of neonates with severe asphyxia was low in our study, the comparison of the ratio in varying severity of HIE could not be done.…”
Section: Discussionmentioning
confidence: 80%